Cellular activity of Wharton's Jelly‐derived mesenchymal stem cells on electrospun fibrous and solvent‐cast film scaffolds. Issue 1 (18th September 2015) - Bagher, Zohreh; Ebrahimi‐Barough, Somayeh; Azami, Mahmoud; Safa, Majid; Joghataei, Mohammad Taghi
Abstract: It was shown that topography and surface chemistry of materials influence cell behaviors. In this study, the effects of chemistry and topography of scaffold surface on adhesion, proliferation and differentiation of Wharton's Jelly mesenchymal (WJMSCs) stem cells into motor neurons were investigated. WJMSCs were cultivated in an neurogenic inductive medium on the surface of modified and unmodified polycaprolactone (PCL) electrospun fibrous and solvent‐cast film scaffolds. All the scaffolds were characterized according to their ability to support cell attachment and viability by SEM and MTT assay. The expression of motor neuron‐specific markers was assayed by real‐time PCR after 15days post induction. Results showed that attachment, proliferation and differentiation of WJMSCs into motor neuron‐like cells on the nanotopographic surface was higher than that of the cells on the solvent‐cast scaffolds. In addition, regardless of their topography, WJMSCs cultured on collagen‐coated PCL nanofibrous showed results similar to collagen‐coated PCL films. Results suggested that surface chemistry has more impact on WJMSCs behaviour rather than topography. In conclusion, collagen‐coated electrospun PCL have potential for being used in neural tissue engineering because of its bioactive and three‐dimensional structure which enhance viability and differentiation of WJMSCs. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 218–226, 2016.